A SWARA method to analyze the risks in coal supply chain management. (2022) - Sivageerthi, T.; Bathrinath, S.; Uthayakumar, M.; Bhalaji, R.K.A.
Abstract: Recently coal supply chain has obvious benefits regarding stability, economy and safety. But issues increased in the coal supply chain management (CSM) process greatly impacted organizational performance. Therefore, one of the key problems in CSM is identifying and prioritizing the various risks and finding suitable solutions for encountering them at the time of risk occurrence. The objective of the paper is to determine the most influential risk in the context of the South Indian Thermal power plant. For this purpose, a multi-criteria decision-making (MCDM) based stepwise weight assessment ratio analysis (SWARA) method has been used to investigate the CSM risks. Based on the Delphi method, thirteen CSM risks were identified. As per the method SWARA, the relative weight of each risk was computed. The findings indicated that power plant-specific fuel consumption, the geographical location of plants from mines, and the quality of coal are the most influential ones. In addition to this, this paper provides some useful implications for managers in the industry regarding organizational performance implementation.